Practice resource‐focused revision: Standardized pedigree nomenclature update centered on sex and gender inclusivity: A practice resource of the National Society of Genetic Counselors. Issue 6 (15th September 2022) - Bennett, Robin L.; French, Kathryn Steinhaus; Resta, Robert G.; Austin, Jehannine
Abstract: This focused revision builds on the expert opinions from the original publications of 'Recommendations for human standardized pedigree nomenclature' published in 1995 and updated in 2008. Our review of medical publications since 2008 did not identify any fundamental systematic alternative pedigree nomenclature. These findings attest to the relevance of most of the nomenclature with the critical exception of the nomenclature used to denote sex assigned at birth and gender. While we are not recommending the creation of any new pedigree symbols, a major focus of this publication is clarification of the use of symbols and language in the description of the distinction between sex and gender, with a view to ensuring safe and inclusive practice for people who are gender‐diverse or transgender. In addition, we recommend modifications to the way that carrier status is depicted. Our goal is to respect individual differences and identities while maintaining biologically, clinically, and genetically meaningful information.